Short-termism in social organizations - El Armali, Jafar (Journal of Economics and Business Letters, 2025)
Social organizations, defined as social entrepreneurship and nonprofit organizations, aim to meet societal objectives and play an important role in achieving sustainable development goals (SDGs). However, social organizations may fall into short-termism, defined as favoring short-term goals over long-term objectives. This undermines social organizations’ ability to meet their long-term objectives and, in turn, negatively affects efforts to meet sustainable development goals. This note presents the channels that contribute to short-termism in social organizations. Three channels are presented and discussed herein. First, if investors and donors are short-term oriented, social organizations may focus on meeting short-term goals over long-term objectives to satisfy the demands of investors and donors and attract their funding. Second, if the management of a social organization is short-term oriented, it will be inclined to prioritize short-term goals over long-term objectives. Third, scaling up operations may result in neglecting the long-term objectives of social organizations. Understanding the roles of these channels is important for providing a better understanding of short-termism in social organizations.